Association of body composition with left ventricular remodeling and outcomes in diabetic heart failure with reduced ejection fraction: assessment of sarcopenic obesity using cardiac MRI - Ke Shi; Ge Zhang; Rong Xu; Xue-Ming Li; Li Jiang; Yue Gao; Hua-Yan Xu; Yuan Li; Ying-Kun Guo; Zhi-Gang Yang (Cardiovascular Diabetology)
Abstract Background Obesity is common in the heart failure (HF) population and is regarded as an important risk factor for developing HF. Greater skeletal muscle mass has shown to be the underlying protective factor against cardiac failure. Since diabetic mellitus (DM) can impair muscle protein metabolism, leading to skeletal muscle wasting, accompanied by adipose tissue accumulation, sarcopenic obesity (SO) may be a high-risk phenotype with poor outcomes in this specific population, especially in HF with reduced ejection fraction (HFrEF). Thus, the aim of this study was to clarify the clinical profiles, left ventricular (LV) remodeling, and prognostic implications of SO in patients with HFrEF and DM. Methods A total of 283 patients who underwent cardiac MRI were included. Thoracic skeletal muscle index (SMI) was served as a surrogate of skeletal muscle mass. Patients were stratified according to the median thoracic SMI (42.75 cm2/m2) and body mass index (25 kg/m2). Obesity in conjunction with a SMI lower than the median is referred to as SO. The LV volume and function, as well as the systolic strain, were measured. The clinical characteristics and cardiovascular outcomes (heart failure readmission, cardiovascular mortality and heart transplantation) were recorded. Results Patients with SO had a greater level of amino-terminal pro-B-type natriuretic peptide and were more likely than nonsarcopenic patients with obesity to present with hypoproteinemia. Among patients with obesity, those with sarcopenia displayed greater LV expansion and more profound LV dysfunction, together with an increase in LV mass. During a median follow-up duration of 35.1 months, a total of 73 (25.8%) subjects reached the composite endpoint, with a worst outcome in the group of patients with SO (log-rank P = 0.04). Multivariable Cox analysis revealed that patients with SO had an approximately 3-fold greater risk of experiencing adverse outcomes than did those with neither sarcopenia nor obesity (hazard ratio: 3.03, 95% confidence interval: 1.39 to 6.63; P = 0.005). Conclusions SO is a potentially high-risk phenotype with adverse LV remodeling and poor clinical outcomes in diabetic patients with HFrEF that may require more attention.